Diffuse meningeal thickening associated with pleural mesothelioma. Issue 1 (January 1990) - Murray, J B; Neilly, J B; Hadley, D; Moran, F; McKean, M
Abstract : A case of pleural mesothelioma with diffuse spinal meningeal thickening as shown by magnetic resonance imaging is reported.